If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11x + -5x + 1 = 65x + 36 Reorder the terms: 1 + -11x + -5x = 65x + 36 Combine like terms: -11x + -5x = -16x 1 + -16x = 65x + 36 Reorder the terms: 1 + -16x = 36 + 65x Solving 1 + -16x = 36 + 65x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-65x' to each side of the equation. 1 + -16x + -65x = 36 + 65x + -65x Combine like terms: -16x + -65x = -81x 1 + -81x = 36 + 65x + -65x Combine like terms: 65x + -65x = 0 1 + -81x = 36 + 0 1 + -81x = 36 Add '-1' to each side of the equation. 1 + -1 + -81x = 36 + -1 Combine like terms: 1 + -1 = 0 0 + -81x = 36 + -1 -81x = 36 + -1 Combine like terms: 36 + -1 = 35 -81x = 35 Divide each side by '-81'. x = -0.4320987654 Simplifying x = -0.4320987654
| 4p^2+3p-2=0 | | V/7-3.2=-20.7 | | 4p^3+3p-2=0 | | -6x-8=-3 | | x-.125=-.75 | | -3(6s+9)= | | (2-x)+8x=3(x-6) | | (11/2)(-3/2)=19/2 | | 1/8=X-5/12 | | .3x+x=50 | | 6x-5+2=7+9x-3 | | Y-5=(x-2) | | -(z-4)+(2z+1)=-2(z+1) | | 0.5(6g+2)=12 | | -(5x-11)+3(3x+7)= | | 5x-5y-7=0 | | 8.8x+98.58=-11.2x+97.26 | | 8.8+98.58=-11.2x+97.26 | | 4x-31+2x+7=180 | | (6/35)/(2/7) | | 4/u=8/11 | | 180=123+(x-2)+(x-3) | | 5x-3=3(x+7) | | x-.75=.625 | | 24=4t | | x-18/14=.4 | | -9.6=-4/5x | | 8.1x+87.61=-11.9+86.27 | | 6c+2=13 | | 2.4=-x/4 | | 3k-3/3 | | 3=7tx+b |